Environmental biological radiation hazards (ELCR, AED) from background radiation in vitamins consumed by pregnant women in Iraq - Alebadi Shireen N.; Mohammed Torki Wedyan; Saeed Jassim Ali; Kamil Khaleel Hadeel (E3S Web of Conferences)
This study aims to assess the background radiation levels of dietary supplement samples utilised by pregnant women in Iraq. The D, AED, and ELCR values for twenty dietary supplements from this region. The D values (in μSv/h) are (0.15 ± 0.003 μSv/h). The radiation dose outputs from the aforementioned investigations are compared with a safe limit of 0.247 μSv/h established by UNSCEAR 2008 and NCRP 2009. The radiation dosage for all samples in the present investigation unequivocally remains within acceptable thresholds. Furthermore, the AED values derived from μSv/h are (1.290 ± 0.026 mSv/y), which exhibit discrepancies. Figure 3 juxtaposes the corresponding dose rates from this study with a permissible threshold of 2.4 mSv/y, as per UNSCEAR 2008 and NCRP 2009. The data indicate that all AED values found during the sample examination remained below safety limits. Finally, the ELCR×10-3 values vary with a mean value of (4.500±0.085). The radiation background levels in these are considered safe, and their use poses no substantial danger of radiation exposure. The dietary supplements evaluated in this study are deemed safe for pregnant women, posing no possible danger of radiation consequences.